Age Determination of Gem-Quality Green Vanadium Grossular (Var. Tsavorite) from the Neoproterozoic Metamorphic Mozambique Belt, Kenya and Tanzania - Siyi Zhao; Bo Xu; Yi Zhao (Crystals)
Gem-quality garnets, with their high closure temperature (750–800 °C), high transparency, uniform composition, and purity, offer promising prospects for U-Pb dating. Despite decades of recognition that garnets can be dated using the U-Pb method, direct dating remains extremely limited. Tsavorite is a rare gem-quality green vanadium-rich grossular hosted in the Neoproterozoic Metamorphic Mozambique Belt (NMMB). Until now, the accurate crystallization age of the tsavorite in Kenya and Lemshuku (Tanzania) has remained unknown. Here, we conducted in situ laser U-Pb geochronological analysis on gem-quality tsavorite samples from Tanzania and Kenya. U-Pb dating of tsavorite sourced from the Lemshuku mine (Tanzania) and the Tsavorite mine (Kenya) yielded ages of 643.9 ± 3.2 Ma and 617.4 ± 4.8 Ma, respectively. The high closure temperature of the U-Pb system within garnets renders it more inclined to preserve crystallization ages rather than documenting cooling events or metamorphic overprinting. Consequently, these ages are indicative of the tsavorite mineralization epochs. These findings align with the most significant metamorphic period documented in the Mozambique Belt, known as the East African Orogen, which occurred between 640 and 600 Ma. U-Pb data have revealed distinct formation times for each district. Dating specific deposits can provide more precise information about the origin of tsavorite, rather than solely relying on isotope or trace element data that have long been used for provenance studies of tsavorite.